Fluorohalogenation of gem‐Difluoroalkenes: Synthesis and Applications of α‐Trifluoromethyl Halides. Issue 9 (30th January 2020) - Liu, Chi; Zhu, Chuanle; Cai, Yingying; Yang, Zhiyi; Zeng, Hao; Chen, Fulin; Jiang, Huanfeng
Abstract: A novel strategy for 1, 2‐dihalogenation of alkenes is reported that occurs through a sequential nucleophilic halide addition and electrophilic halogenation. By trapping the in situ generated unstable α‐trifluoromethyl carbanion intermediates derived from the nucleophilic fluoride addition to electron‐poor gem ‐difluoroalkenes, this fluorohalogenation of gem ‐difluoroalkenes with electrophilic haloalkynes affords various useful α‐trifluoromethyl halides in high yields. A pesticidal active compound and various attractive trifluromethylated molecules could be smoothly synthesized from these obtained α‐trifluoromethyl halides. Abstract : Facile 1, 2‐dihalogenation ! The fluorohalogenation of gem ‐difluoroalkene is reported that is initiated by nucleophilic fluorination and followed by electrophilic halogenation of the in situ generated unstable α‐trifluoromethyl carbanion. The obtained α‐trifluoromethyl halides were further transformed into various useful trifluoromethylated compounds.